Developing a Medium Term Strategy (MTS) 2011-2015 for the Caribbean Regional Agricultural Policy Network (CARAPN) - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Technical Centre for Agricultural and Rural Cooperation, 2010)
The origin of CaRAPN was an idea suggested by the CTA in 2002, discussed and agreed to at a regional meeting in 2003 and operationalised as a project between IICA and the CTA later that same year... This meeting provides the opportunity to expand that partnership and provide the base for strengthening and sustaining the networking.